Parents' awareness on child abuse among the staff in UiTM Kedah / Nur Syamimi Mohd Sukery and Nor Ain Mahmood - Mohd Sukery, Nur Syamimi; Mahmood, Nor Ain (2019)
As a parents, awareness on the children in every perspectives are naturally have in every people called as parents'. However, for certain circumstances, parents may be lack in terms of awareness due to certain reason. Thus, this study is conducted to know the extent of parents' awareness on child abuse. Since nowadays the cases of child abuse keep arising and reported by the media, the researcher do think that this study can help the parents to have a knowledge or increase the awareness on child abuse. The children safety need to be safeguard by the society especially the parents itself. The quantitative method is being used to measure the extent of awareness and the result are shown in the findings.